2022
DOI: 10.1186/s40066-022-00378-1
|View full text |Cite
|
Sign up to set email alerts
|

The drivers and intensity of adoption of beekeeping in northwest Ethiopia

Abstract: Background Beekeeping activity is carried out in most parts of Ethiopia. However, despite the favorable agro-ecology for beekeeping practices and the high number of bee colonies the country is endowed with, the level of beekeeping adoption is low. Methods This study was conducted to identify determinants of the decision to adopt beekeeping, and the intensity of adoption by using a cross-sectional data collected from 772 rural households in Northwes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Thus, embracing new technologies attracts higher returns in the households. This was a contrast to Andaregie et al (2022) who reported that rural households located far away from marketplace get limited information and have difficulties in accessing inputs for apiculture.…”
Section: Multiple Linear Regression Results On Adoption Of Modernmentioning
confidence: 58%
See 1 more Smart Citation
“…Thus, embracing new technologies attracts higher returns in the households. This was a contrast to Andaregie et al (2022) who reported that rural households located far away from marketplace get limited information and have difficulties in accessing inputs for apiculture.…”
Section: Multiple Linear Regression Results On Adoption Of Modernmentioning
confidence: 58%
“…However, Bojago (2023) found a positive influence stating that larger families are more likely to use modern technologies in order to meet their daily needs. Correspondingly, Andaregie et al (2022) reported that those households with large family size are likely to produce more honey and adopt new technologies since there is availability of more labour to look after the enterprise.…”
Section: Multiple Linear Regression Results On Adoption Of Modernmentioning
confidence: 99%
“…However, the beekeeping system remains predominantly traditional and, hence, its contribution to the local community, national economy, and the country's international trade stays minimal [14]. Ethiopia is known for its greatly diversified agroclimatic conditions and biodiversity, which caused the presence of abundant honeybee flora and a massive number of honeybee colonies [19][20][21][22][23]. It is estimated that the country has a total of 10 million Apis mellifera bee colonies.…”
Section: Introductionmentioning
confidence: 99%